PERTANGGUNGJAWABAN TINDAK PIDANA TERORISME DALAM PENERBANGAN (STUDI KASUS ANCAMAN BOM DALAM PESAWAT LION AIR JT 687 DI BANDARA SUPADIO PONTIANAK) - Reyhan Hafiz Setiawan, - (2019)
Bomb threats in the aircraft occur a lot but often legal processes are not carried out properly even though there are three laws that can reach the case of bombing jokes in an airplane that is KUHP, Act No. 1 of 2009 concerning flights and Act No. 15 of 2018 concerning terrorism. In the case of an airplane bomb threat in Pontianak, the perpetrators were held accountable for crimes by the adoption of Act No. 1 of 2009 Problems regarding the provisions of application of the terrorism law on the case of joking bombs on the plane and how they were held accountable using normative juridical research method. Suggested to law enforcers, the case of bomb jokes in the airplane can be applied by terrorism laws with specific restrictions or criteria that need to be considered, Furthermore, the author recommends that law enforcers dare to take responsibility for these crimes by applying Act No. 5 of 2018 concerning Terrorism